Vegetation changes and climate shift during the latest Ladinian to the early Carnian: Palynological evidence from the Yanchang Formation, Ordos Basin, China - Li, Xiang; Zhang, Ying; Sun, Yuewu; Shi, Xiao; Zhang, Shuqin (Frontiers in Earth Science, 2023)
The Middle – Late Triassic climates have attracted the attention of paleontological and geological scientists for the Carnian pluvial event in the early Late Triassic. The event is well-documented in the pelagic and epi-continental marine deposits of Tethys, Gondwana, and Laurasia. However, for the inland terrestrial deposits, it is less frequently depicted with high-resolution palynological biostratigraphy constrains. In this study, we report the palynological records from the YC8-1 and YC7-3 members on Yunmeng profile in Ordos Basin, China, where the YC7-3 was dated as 236.0 - 234.1 Ma. Two palynological assemblages were recognized and named after Lundbladispora watangensis–Taeniaesporites combinatus assemblage and Lundbladispora communis–Discisporites granulus assemblage forthe YC8-1 and YC7-3 sub-members, respectively. Their ages were determined to be the latest Ladinian and early Carnian, respectively, for the stratigraphic correlations with the global boundary stratotype section and point (GSSP) of the base of Carnian at Europe and additional co-occurred floras with condonts in the Upper Triassic of South China. The coexistence of Cyathidites minor Couper, 1953, Dictyophyllidites harrisii Couper, 1958, Apiculatisporis bulliensis Helby ex De Jersey, 1970, Aratrisporites xiangxiensis Li et Shang, 1980, Piceaepollenites omoriciformis (Bolkh.) Xu et Zhang, 1980, Podocarpidites ornatus Pocock, 1962, Discisporites granulus Zhang, 1984, and Classopollis Pflug, 1953, is equivalent to the Carnian palynostratigraphy criterion reported in the North China palynofloristic realm. Vegetation changes, especially those occurred at the boundary between Ladinian and Carnian, for approximately 70% ferns and over 30% gymnosperms lost, were discovered and attributed to the strong seasonal arid climate, which has been indicated by the emergence of Cheirolepidiaceae and Pinuspollenites. Thus to know that the climate during the latest Ladinian and early Carnian was “hot house” with seasonal arid. In addition, three strong monsoonal pluvial pulses signaled by the humid index of lowland plants. The present study will allow for a better understanding the Carnian pluvial event in the inland basin in the Late Triassic.